HEALTH COMMUNICATION FOR PHYSICAL ACTIVITY PROMOTION TO ADDRESS OBESITY - Webb, Malayna (My University, 2022)
Background: There is a high prevalence of obesity globally, nationally, and statewide in Kansas with positive trends indicating increasing levels of obesity and physical inactivity for the future. There is a direct, independent, positive correlation between sedentary behavior and obesity. Additionally, there is a separate negative correlation between physical activity (PA) levels and obesity prevalence. These factors working separately to increase the burden of physical inactivity and obesity indicates the need for more thorough intervention to prevent obesity and promote healthy behaviors such as physical activity, and it is imperative to increase reach and effectiveness of such promotion. The use of mass media for PA promotion is plausible for many reasons including cost-effectiveness and widespread reach. Theories such as the competency-opportunity-motivation (COM-B) model of behavior, behavior change wheel, and Theory of Planned Behavior are useful tools with which PA communication interventions can be shaped. Methods: I completed a project with the Wichita Health and Wellness Coalition and K-State Research and Extension; for the purpose of this report, I will focus on my work with the Wichita Health and Wellness Coalition. This project focused on completing three products including social media PA promotion, newsletter content, and a summary of coalition strategies for strategic planning. Results: At the end of this project the Facebook numbers were steadily increasing, and there was no updated number of views and clicks resulting from the newsletter. The summary of coalition strategies was almost fully completed with the exception of a few no-responses; it was turned over to the strategic planning committee for further development of a plan. Discussion: This project was very informative to my professional skills and developed my practical application skills of competencies acquired through the MPH program. There were limitations including the length of the project in relation to the communication campaign portion. Another limitation was the lack of evaluation; there are many ways to evaluate the impact of the messages created if this project were repeated or for future projects, and this would also help to further develop the messages.
Keywords: Physical Activity Promotion; Health Communication; COM-B Model; Behavior Change Wheel; Theory of Planned Behavior